Persepsi Peserta Didik Tentang Interaksi Edukatif Guru Dan Pengaruhnya Dalam Membentuk Kepribadian Muslim (FAI- Undar, 2022)
This study aims to determine the perceptions of students about teacher educative interactions and their influence to formalize of the Muslim personality of students at MI Madinatul Ulum, Mojokrapak Village, Tembelang District, Jombang Regency. The research population is students of 4th, 5th, and 6th grades. The research sample is 156 students. Data collection which used is a questionnaire. Analysis of the data which used is with help by SPSS statistical application software, with the following procedures: descriptive analysis, normality test, linearity test, and correlation test. The final result is hypothesis testing using simple regression analysis (simple regression). The results of the study can be stated as: First, the students' perception states that the educative interactions of teachers at islamic school are going well and the Muslim personality of the students is also well formed; Second, the results of the normality test point that the data is normally distributed out; Third, the results of the linearity test point that there is a linear relationship out between the educational interaction variables and the Muslim personality; Fourth, the results of the correlation test point that there is a significant correlation out between the educative interactions of teachers and the Muslim personality of students; Fifth, the results of hypothesis testing indicate that: (a) teacher educative interaction variables contribute 73.4% to changes in the Muslim personality of students, (b) teacher educative interactions has a significant effect on the Muslim personality of students, (c) The coefficient of positive regression direction which means that every increase in teacher educative interactions will also be followed by an increase in the Muslim personality of students at MI Madinatul Ulum, Mojokrapak Village, Tembelang District, Jombang Regency. Based on the results of this study, it is determined that the educative interaction of teachers contributes greatly to formalize the Muslim personality of students. Therefore, it needs to be studied and or studied further, especially by teachers at islamic school. Eventually, teachers who are part of islamic school- which incidentally are Islamic educational institutions - are expected to really be able to